PERIPHERAL OSTEOMA OF THE HARD PALATE: A RARE CASE REPORT AND LITERATURE REVIEW - Melek RAMOĞLU; Saim YANIK; Zehra BOZDAĞ; Mutan Hamdi ARAS (Istanbul University, 2016)
Osteomas are benign osteogenic tumors that are composed of cancellous or compact bone. They are usually sessile tumours composed of dense sclerotic, well-formed bone projecting out from the cortical surface. They commonly occur in skull and facial bones, however, excluding the maxillary sinuses, the maxilla is a rare site for osteomas. Therefore, we aim to present a case of maxillary osteoma in a 19-year-old male patient and to provide an overview of current literature on the diagnostic options and treatment modalities. To best of our knowledge, in the English literature, this is the seventh reported case of maxillary osteoma which is located on the hard palate.